A new protocol for assessing the conservation priority of groundwater‐dependent ecosystems. Issue 8 (27th July 2020) - Fattorini, Simone; Fiasca, Barbara; Di Lorenzo, Tiziana; Di Cicco, Mattia; Galassi, Diana M. P.
Abstract: Species of conservation concern are usually considered important elements in site prioritization for biodiversity conservation. To overcome the lack of information on species conservation status, multidimensional measures of species rarity can be used as proxies of species vulnerability. Under this assumption, a two‐step protocol for site prioritization of aquatic groundwater‐dependent ecosystems is proposed using invertebrate vulnerability estimated from species' traits. In the first step, each species occurring in the sites of interest are scored according to their vulnerability. In the second step, sites are prioritized using species' scores. Species vulnerability scores are based on five dimensions, for which various traits are scored: (i) geography, (ii) ecology, (iii) biology, (iv) population, and (v) evolutionary history. For each species, the scores of the various traits belonging to the same dimension are multiplied to obtain a synthetic score. These scores are then ranked into four classes and, for each dimension, each species receives a new score that reflects its rank. The sum of these scores represents the species' overall score. Site conservation priorities are assessed by combining species scores into three indices: Sum of Species Scores, Biodiversity Conservation Concern (which relates the sum of species scores with the local species richness) and Groundwater Biodiversity Concern (which is the average of the former two). The protocol is illustrated using case studies in Italy and it is fully implemented in the software AQUALIFE which is freely available at: http://app.aqualifeproject.eu by registered users. Sensitivity analyses showed that the protocol is robust against the lack of information on species biology or sampling limitations. However, trait scoring rests with the user, who must be familiar with the study group. This approach can be applied at any spatial scale and to different types of aquatic groundwater‐dependent ecosystems.